ANALISIS DETERMINAN IMPOR DAGING SAPI DI INDONESIA PADA TAHUN 1990 – 2015 - Chisilia, Linanda Aninditha; Widanta, A.A Bagus Putu (Buletin Studi Ekonomi; VOL.24.NO.2.AGUSTUS 2019, 2019)
Abstract: Determinant Analysis of Beef Import in Indonesia On Year 1990-2015. The purpose of this study is to determine the effect of the amount of production, consumption, prices of imported and local beef and the US dollar exchange rate simultaneously on beef imports in Indonesia. To determine the effect of the amount of production, consumption, prices of imported and local beef and partially the US dollar exchange rate on beef imports in Indonesia. To find out the dominant variable between the amount of production, consumption, the price of imported and local beef and the exchange rate of the United States dollar towards Indonesian beef imports. The data used in this study are secondary using multiple linear regression analysis techniques. The results show simultaneously a significant effect on beef imports in Indonesia. Partially the amount of production and the US dollar exchange rate does not have a significant effect on beef imports in Indonesia. While the variable local prices and consumption partially have a positive and significant effect on beef imports in Indonesia and the import price variable partially has a negative and significant effect on beef imports in Indonesia. The dominant factor affecting beef imports in Indonesia is consumption variable. Keywords: tourism industry; investment; employment opportunities; tourism sector GRDP.